Juvenile idiopathic arthritis with systemic onset with inflammatory bone lesions: two case reports of patients successfully treated with canakinumab and experience gained from literature - Alexeeva, Ekaterina I.; Dvoryakovskaya, Tatyana M.; Tsulukiya, Irina T.; Kondrateva, Natalia M.; Solomatina, Natalia M.; Kondratiev, Gleb V.; Peshekhonova, Luliia V.; Kostik, Mikhail M. (Frontiers in Pediatrics, 2023)
Non-bacterial osteomyelitis (NBO) is a rare chronic inflammatory bone disease, related to immune system dysregulation. The disease belongs to a family of autoinflammatory diseases. Usually, it may coexist with other TNF-a-mediated immune-mediated diseases, such as juvenile idiopathic arthritis (JIA), and inflammatory bowel diseases. The interleukin-1-driven inflammation was described predominantly in monogenic cases of NBO, such as DIRA syndrome or Majeed syndrome. The association between NBO and JIA with systemic onset (soJIA) has not been described yet. Herein we describe two cases of soJIA with inflammatory bone lesions where canakinumab (anti-interleukin-1β antibodies) caused the remission. Case descriptions: Patient 1 - 6 months old boy with typical soJIA had destruction of the 7th-9th ribs, and left pubic bone. Antibiotics, IVIG, and cyclosporine were ineffective. Corticosteroids were effective, but due to corticosteroid dependence, canakinumab 4 mg/kg every 4 weeks initiated and completely controlled the disease and allowed to taper corticosteroids. Patient 2 – a 2-year-old girl developed chronic non-bacterial osteomyelitis of the 5th rib two months after taking corticosteroids prescribed for typical soJIA. She had surgical debridement removal, and several courses of antibiotics were ineffective. She developed macrophage activation syndrome, anakinra was prescribed with temporal improvement and was switched on to canakinumab causing the corticosteroid-free remission. Conclusion: This is a first description of a rare association of soJIA with inflammatory bone lesions with the proven efficacy of IL-1 blockade. The association of two autoinflammatory conditions should indicate the IL-1-driven mechanisms and possible genetic basis. Followed genetic and functional studies are required to better understand the pathogenesis of such overlapping diseases.